PM.101 Locally Invasive Oesophageal Adenocarcinoma Diagnosed in the Second Trimester, the Options. (26th April 2013) - Hodson, K; Lyon-Dean, C; MacDougall, MWJ
Abstract : Oesophageal cancer is a rare malignancy to present during pregnancy. Standard treatment outside of pregnancy involves three cycles of Cisplatin, Epirubacin and 5 Flurouracil, a combination rarely used in pregnancy, followed by oesophagectomy in week 15 of treatment. We aim to highlight the management dilemmas posed by such cases, balancing the risk of treatment options in trying to achieve the best outcome for both mother and baby. We present the case of a 31 year old primiparous woman diagnosed at 23 weeks gestation with locally invasive oesophageal adenocarcinoma. Delay in chemotherapy treatment with early delivery by Caesarean section risked disease progression to an inoperable stage for mum, and the risk of prematurity for baby. We elected to start three cycles of the standard chemotherapy regime without delay, with increased fetal surveillance. Maternal anaemia developed. Prostaglandin induction took place at 37 + 2 weeks gestation, resulting in a forceps delivery of a live 2050 g male infant with Apgars of 9 and 9 at one and 5 minutes. Neonatal full blood count was normal at 12 hours of age. Postnatal staging confirmed the lesion was still operable and oesophagectomy took place at the usual chemotherapy surgery time interval. Good tumour margins were achieved and the patient returned home on day ten. We discuss our rational not to delay treatment with early delivery by Caesarean section, accepting the risk of chemotherapy in pregnancy. We review the literature surrounding this cocktail of chemotherapeutic agents and discuss the dilemmas surrounding the treatment of her anaemia.